Proportions of circulating T cells with a regulatory cell phenotype increase with HIV-associated immune activation and remain high on antiretroviral therapy - Lim, A.; Tan, D.; Price, P.; Kamarulzaman, A.; Tan, H.Y.; James, I.; French, M.A. (2007)
Objective: To examine the relationships between blood CD4 natural regulatory T (T-reg) cells, plasma HIV RNA level, CD4 T-cell count and immune activation in untreated HIV-infected patients and immunodeficient patients beginning antiretroviral therapy (ART), using a novel phenotype to define Treg cells (CD25CD127(lo)CD4). Data were compared with established T-reg cell markers (FoxP3, CTLA-4 and GITR). Methods: Twenty-nine untreated HIV-infected patients with CD4 T-cell counts of < 300 or > 400/mu l were compared in a cross-sectional study and 12 patients beginning combination ART with < 100 CD4 T cells/mu l were followed for 1 year on therapy. Three- and four-colour flow cytometry was used to quantitate proportions of Treg cells. Results: In control donors and patients with high CD4 T-cell counts, 28-89 (median 60) of CD25CD127(lo)CD4 cells were FoxP3, but < 10 expressed GITR or CTLA-4. Immunodeficient patients also had CD4-negative lymphocytes with the phenotype FoxP3CD127(lo). Proportions of CD25CD127(lo) cells and activated (HLA-DRhi) cells in the CD4 T-cell population were increased in patients with low CD4 T cell counts. The proportion of CD25CD127(lo)CD4 T cells correlated positively with plasma HIV RNA level and CD4 T-cell activation, but inversely with CD4 T-cell count. Longitudinal studies of 12 patients receiving ART in two distinct cohorts (Western Australia and Malaysia) showed that the proportion of CD25CD127(lo)CD4 cells decreased slightly over time, but remained above levels seen in non-HIV controls. Conclusions: Proportions of circulating T cells with a regulatory cell phenotype increase with HIV-associated immune activation and remain high after I year on ART. (c) 2007 Lippincott Williams & Wilkins.